Consumers' Research on Cosmetic Brands Preference and Purchasing Behavior: Thai Brands and Chinese Domestic Brands - Nico Irawan; Cai Yun Pu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2020)
The research theme is put forward under the realistic background of the development of Thai cosmetics in the Chinese market. Intends to start from cosmetics, with some college students and working youth groups as samples to study the evolution of Thai cosmetics in the Chinese market. Based on reviewing the research results of related topics at home and abroad, this paper draws on the classic consumer ethnocentrism and Chinese goods purchasing behavior relationship model, collects data through questionnaires, and uses SPSS data analysis software to trust the recovered data, validity test, and regression analysis to test each hypothesis. The results confirmed the consumer's relationship between the category of cosmetics, Chinese goods awareness and brand preference, brand identity perception and purchase, and their variables in the context of Chinese and Thai brands.